2018
DOI: 10.1002/jcp.26383
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MALAT1 induces colon cancer development by regulating miR‐129‐5p/HMGB1 axis

Abstract: Recent studies have exhibited significant roles of lncRNAs in various tumors' development, including colon cancer. Our study focused on the biological roles of lncRNA MALAT1 in colon cancer. In our study, it was demonstrated that MALAT1 was upregulated in human colon cancer cell lines including Lovo, HCT116, SW480, and HT29 cells compared to the normal human intestinal epithelial HIEC cells. Moreover, we observed that miR-129-5p was downregulated in colon cancer cells with a significant increase of HMGB1 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
105
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(110 citation statements)
references
References 41 publications
2
105
0
Order By: Relevance
“…The diminished expression of miR‐129 in MM cell lines was further explored. MiR‐129 was reported previously to be regulated by lncRNAs . In this study, we for the first time demonstrated a direct link between PCAT‐1 and miR‐129 in MM and that the PCAT‐1 level in MM‐derived PCs was significantly higher than that in the control and negatively associated with the level of serum miR‐129.…”
Section: Discussionsupporting
confidence: 62%
“…The diminished expression of miR‐129 in MM cell lines was further explored. MiR‐129 was reported previously to be regulated by lncRNAs . In this study, we for the first time demonstrated a direct link between PCAT‐1 and miR‐129 in MM and that the PCAT‐1 level in MM‐derived PCs was significantly higher than that in the control and negatively associated with the level of serum miR‐129.…”
Section: Discussionsupporting
confidence: 62%
“…[3][4][5][6][7][8][9] LncRNAs are noncoding RNAs with a length of more than 200 nt, as ceRNAs, which further regulated the production of downstream proteins by regulating the miRNA/mRNA axis. [10][11][12][13] Some lncRNAs have been reported to be differentially expressed in colorectal cancer tissues and cells, but their functions have been verified. 14 For example, lncRNA DLEU1 promoted CRC cell progression through regulating KPNA3.…”
Section: Introductionmentioning
confidence: 99%
“…miR-129-5p participated in a ceRNA pathway in colon cancer. 35 miR-181a-5p and multiple myeloma progression. 36 All above examples showed the interaction between miRNAs and mRNA in cancers.…”
Section: Discussionmentioning
confidence: 99%